The Origin and Consequences of Sebiran Community COVID-19 Case - Abdulah, Deldar Morad; Saeed, Mahir Sadullah (International Journal of Human and Health Sciences (IJHHS), 2021)
On March 2, 2020, the Ministry of Health announced four confirmed cases of COVID-19 with travel history. The health departments in Iraqi Kurdistan started to identify and monitor all individuals considered with close contact with confirmed COVID-19 patients. An individual who returned to the Sebiran community (in Erbil) from Iran on February 16, 2020, without announcing the authorities and later was tested positive for the coronavirus. The asymptomatic person behaved normally with other persons as a healthy person since his return. The health authorities reported that by March 24, 2020, 15 persons of this community had been affected among the first 200 tests. The confirmed cases were his wife and son (5 years old), neighbors who had close contact with the confirmed case, persons with household exposure, and community members with indirect contact with the case. The strict lockdown and curfew were applied to the Sebiran community for 14 days. Following March 24, 2020, no positive case was identified among the performed cases in the community. Accordingly, on 5/4/2020, the quarantine of the community was lifted. The success of the KRG is summarized in: timely quarantine, active surveillance/active symptom monitoring, and social distancing. International Journal of Human and Health Sciences Vol. 05 No. 03 July’21 Page: 355-357